2022
DOI: 10.3390/foods11172592
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Functional Properties, and Cytoprotective Effects on HepG2 Cells of Tree Peony (Paeonia suffruticosa Andr.) Seed Protein Hydrolysate as Influenced by Molecular Weights Fractionation

Abstract: In recent years, plant protein hydrolysates have gained increased attention due to their superior antioxidant activity and potential to prevent several chronic diseases associated with oxidative stress. This study aimed to investigate the antioxidant activity, functional properties, and cytoprotective effects of the tree peony seed protein hydrolysate (TPSPH) with different molecular weights (MWs). The antioxidant activities were evaluated by DPPH, hydroxyl radicals scavenging, Fe2+ chelating, and inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In addition, the size of the peptide has an effect on its antioxidant activity; the low molecular weight peptide (less than 10 kDa) easily interacts with free radicals and is good for adsorption in cells [41,42]. showed no toxicity toward both cell lines at 0.98-62.50 µg/mL, however at higher concentration (125-500 µg/mL), it showed slight toxicity that was significantly different from that of the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the size of the peptide has an effect on its antioxidant activity; the low molecular weight peptide (less than 10 kDa) easily interacts with free radicals and is good for adsorption in cells [41,42]. showed no toxicity toward both cell lines at 0.98-62.50 µg/mL, however at higher concentration (125-500 µg/mL), it showed slight toxicity that was significantly different from that of the control group.…”
Section: Resultsmentioning
confidence: 99%
“…WB-G protein hydrolysate was shown to have high antioxidant activity and can donate electrons to free radicals or ROS to decrease the damage of H2O2 [49]. In addition, the molecular weight of protein hydrolysate from WB-G was smaller and could more easily interact with free radicals and halt the chain Functional Foods in Health and Disease 2023; 13(4): 208-224 FFHD Page 218 of 224reaction to prevent damage to essential chemicals[50].Watermelon seed protein hydrolysate with low molecular weight proteins or peptides (5-10 kDa)showed a cytoprotective effect against H2O2 in the HepG2 cell line[42]. Soybean protein hydrolysate protected Caco-2 cells against H2O2-induced oxidative damage by downregulating ROS in the cell[51].…”
mentioning
confidence: 99%
“…These cells are sensitive to cytotoxic effects and are therefore widely used in test systems in original studies of promising pharmacological drugs [ 48 ]. When studying the systemic metabolism of drugs, cell lines of hepatocyte origin are used, such as the HepG2 cell line [ 49 , 50 , 51 ], which we used to determine the possible risks of the applied combination of ascorbic acid and lysozyme hydrochloride on SH-groups, TBA-active components, and catalase activity as important indicators of antioxidant protection. MAEC line was used as a model system that plays an important role in the endothelial barrier of drug permeability [ 52 , 53 ] to determine possible changes in the morphofunctional features of these cells under the action of ascorbic acid and lysozyme hydrochloride.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the molecular weights of prolamins from highland barley are significantly larger than those in zein. Almost all physico-chemical properties of proteins, including viscosity, emulsifying property, gel property, and filming-forming properties, etc., are closely related to the molecular weight [ 15 , 16 ]. This indicates that prolamins from highland barley may exhibit quite different functional properties from zein.…”
Section: Resultsmentioning
confidence: 99%